A Thioxanthone-Based Visible Photoinitiator - Dogruyol, Sevnur Keskin; Dogruyol, Zekeriya; Arsu, Nergis (WILEY, 2011)
Thioxanthone-based 9-(2-Morpholine-4yl-acetyl)-5-thia-napthasen-12-one (TX-MPM) was synthesized and characterized as a one-component novel visible photoinitiator. Its capability to act as an initiator for the polymerization of methyl methacrylate (MMA) was examined in photoreactor and also daylight. Photophysical properties: fluorescence and phosphorescence emission spectra and fluorescence quantum yield of TX-MPM (Phi(f) = 0.29) were determined. The phosphorescence lifetime was found 131 ms for TX-MPM and 110 ms for initiator-attached polymer (PMMA) at 77 K, indicated a pi ->pi* nature of the lowest triplet state. A model compound, morpholino acetonapthone was used as quencher for the triplet states of TX-MPM and the quenching rate constant was determined (k(q) = 1.26 x 10(9) M(-1)s(-1)). According to laser flash photolysis studies, intermolecular hydrogen abstraction process was more dominant path to the formation of the initiating radicals. (C) 2011 Wiley Periodicals, Inc. J Polym Sci Part A: Polym Chem 49: 4037-4043, 2011
Keywords: initiators; photochemistry; photopolymerization; FREE-RADICAL POLYMERIZATION; CHAIN THIOXANTHONE; COINITIATOR; MACROPHOTOINITIATOR; METHACRYLATE; GELATION; AMINE; ACID; Polymer Science